Penerapan Pajak Pertambahan Nilai Berdasarkan PMK No.121/PMK.003/2015 atas Transaksi Ekspor Impor pada Perusahaan Freight Forwarding : Studi Kasus : PT. Leschaco Logistic Indonesia - Karniawan, Nanda; Syahzuni, Barlia Annis (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this research is to determine of the implementation of value added tax (VAT) for an export and import transaction in a freight forwarding company based on PMK NO.121/PMK.003/2015. The result of this research is that for transaction export and import that has been running from the company that already appropriate to the regulation of PMK NO.121/PMK.003/2015. The export and import transaction is already using the rate of 10% x10% from the tax base amount as a refer to PMK NO.121/PMK.003/2015. Every purchase and sell transaction is already record in SAP from the receivable and payable until the transaction is paid. The company should report all the transaction from the purchase till selling in the VAT report. To complete the payment, the company should pay the owed VAT first then the customer will pay base on payment term and the company has a strong cash flow to complete the payment of VAT report